2024
DOI: 10.3390/s24030952
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Corrected Calibration of GS3 and TEROS-12 Soil Water Content Sensors

Paolo Nasta,
Francesca Coccia,
Ugo Lazzaro
et al.

Abstract: The continuous monitoring of soil water content is commonly carried out using low-frequency capacitance sensors that require a site-specific calibration to relate sensor readings to apparent dielectric bulk permittivity (Kb) and soil water content (θ). In fine-textured soils, the conversion of Kb to θ is still challenging due to temperature effects on the bound water fraction associated with clay mineral surfaces, which is disregarded in factory calibrations. Here, a multi-point calibration approach accounts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Nasta et. al., [8] examined two soils (loamy and clay) and showed that the application of soil-specific temperature correction is highly recommended, if the TEROS 12 is installed in regions with pronounced seasonal variations in soil temperature.…”
Section: Background Work and Motivationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nasta et. al., [8] examined two soils (loamy and clay) and showed that the application of soil-specific temperature correction is highly recommended, if the TEROS 12 is installed in regions with pronounced seasonal variations in soil temperature.…”
Section: Background Work and Motivationsmentioning
confidence: 99%
“…The latter values, along with the original triplet (i.e., the VWC, temperature and the bulk conductivity values) were forwarded to a laptop, connected to the microcontroller via a USB connection, for storage and further processing and/or visualization, typically utilizing the MS Excel application. Sensor-to-sensor variability effects were ignored in our work by crudely assuming limited sensor-to-sensor variability, similar to Nasta et al in [8].…”
Section: Measurement In Soilsmentioning
confidence: 99%
See 1 more Smart Citation